The modern art and science of mobility - Broussal-Derval, Aurélien; Ganneau, Stephane (Human Kinetics, 2020)
The Modern Art and Science of Mobility explains and illustrates more than 300 exercises designed to improve recovery, reduce pain, improve mobility, and activate muscles